(untitled) (Andamios, Revista de Investigación Social, 2025)
Police violence against black bodies in peripheral territories is the central focus of the article. To understand it, we seek to analyze the relationship between racism and racial capitalism in peripheral regions of Brazil. The text presents statistical data on homicides in this population collected in reports from the Center for Security and Citizenship Studies and the Atlas of Violence of the Institute for Applied Economic Research, interpreting them in light of discussions on racial capitalism and racism. Understanding police violence as a multi-causal phenomenon derived from racism, the macro cause of this situation being the result of the idea of ​​race that has been built since colonial times in Brazil. In this way, this article serves as a tool to combat the genocide of the black population by police operations, in addition to putting into debate one of the most stigmatized favelas in Salvador – BA, known as Planeta dos macacos. In addition, it is intended to contribute epistemologically against institutional racism, highlighting the need to rethink the political structures of Brazil.